TECHNOLOGY SOCIALIZATION IN THE WORKPLACE: MANAGING CHANGE AND SKILLS IN HUMAN RESOURCE MANAGEMENT - MM Tri Susetyaning Mildawani (SEAN Institute, 2022)
Technology socialization is an important process that allows organizations to introduce and integrate new technologies into the work environment. This affects cultural changes, organizational governance, and requires employee adaptation. This research aims to examine the impact of technology socialization in the workplace in managing change and skills in human resource management . This research uses a qualitative approach with descriptive methods. The research results show that human resource management (HR) has an important role in managing the technology socialization process in the workplace. Close collaboration between HR and information technology (IT) departments is key to understanding an organization's technology needs, ensuring recruitment of individuals with appropriate technical competencies, and designing effective training programs. Regular evaluations are necessary to understand the impact of technology on productivity, while peer support helps employees overcome feelings of discomfort. In addition, creating an organizational culture that supports innovation and acceptance of technology is also the responsibility of HR. Communicative and inclusive change management is a key element in ensuring a successful technology introduction.